RESPON KONSUMEN TERHADAP PRODUK MIE INSTAN INDOFOOD DI ROYAL SWALAYAN SITUBONDO - Rini Kartika Sari (Growth, 2019)
This study aimed to determine the effect either simultaneously or partially between the variable X1 (Sense) and X2 (Price), X3 (Promotion), X4 (Availability of Products) and X5 (Psychological) of the Consumer Response and to determine the effect of the most dominant among the variables X1 (Sense) and X2 (Price), X3 (Promotion), X4 (product availability) and X5 (Psychological) Against Consumer Response. Methods of data collection in this study are primary and secondary methods. Where to data analysis using Regression Methods, F test and t test. Based on the analysis that has been done can be the first conclusions, simultaneously (together) note that the value of Fvalue <Ftable means that Ho accepted and Ha rejected which means no simultaneous effect between the variable X to Consumer Response. Second, partially it is known that X3 (Promotion) and X5 (Psychological) both have a value of tcount > ttable which means there is a partial effect on Consumer Response. And third, the psychological variables that predominantly influence consumer response.